Crossing strategy for breeding campero chickens. An inta-university collaborative project - Canet, Zulma Edith (2021)
Campero chicken is a bird destined to production systems alternative to the industrial one. Campero INTA is a two-way cross between synthetic populations generated by INTA in Pergamino. These populations have remained closed and with a low effective size with the consequent detrimental effect associated with inbreeding depression. To have a dual-purpose population with adequate meat and egg production levels and rusticity to be used in semi-intensive systems that preserve animal welfare, a survey program of the available genetic resource was implemented and a crossbreeding plan to produce a terminal three-way hybrid was designed. The sequence included the evaluation of five maternal synthetic populations (A, E, DE, ES and CE), the selection of two of them (ES and A), their characterization in two-way reciprocal crosses [(ESxA) and (AxES)], the choice of the alternative (ESxA) as female parent and its crossing by roosters of the improved paternal line AH’ to obtain the Campero Casilda chicken as the final product. The evaluation of their growth pattern, body conformation, conversion ratio and productive characters at slaughter indicate that both males and females satisfied the requirements as birds destined for meat production established in the respective protocol. The evaluation of productive characters at sexual maturity, dynamic pattern of egg weight gain and laying curves allowed to qualify the females as layers.